2013
DOI: 10.1016/j.cub.2013.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

An Atypical Tubulin Kinase Mediates Stress-Induced Microtubule Depolymerization in Arabidopsis

Abstract: The rapid and reversible modification of tubulin subunits by PHS1-mediated phosphorylation enables dynamic remodeling of the plant microtubule cytoskeleton in response to external stimuli. Suppression of the potent tubulin kinase activity by the juxtaposed phosphatase domain tightly controls this stress-activated microtubule regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(152 citation statements)
references
References 38 publications
6
145
0
1
Order By: Relevance
“…Null alleles of PHS1 are phenotypically indistinguishable from the wild type under standard growth conditions (Pytela et al 2010), but do not induce MT depolymerization upon hyperosmotic stress (Fujita et al 2013). In addition to the MPK phosphatase domain, PHS1 contains an atypical kinase domain that phosphorylates Thr349 of a-tubulin (Fujita et al 2013). This threonine residue is well conserved among eukaryotic a-tubulins and is located at the longitudinal interdimer interface of the tubulin heterodimer.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Null alleles of PHS1 are phenotypically indistinguishable from the wild type under standard growth conditions (Pytela et al 2010), but do not induce MT depolymerization upon hyperosmotic stress (Fujita et al 2013). In addition to the MPK phosphatase domain, PHS1 contains an atypical kinase domain that phosphorylates Thr349 of a-tubulin (Fujita et al 2013). This threonine residue is well conserved among eukaryotic a-tubulins and is located at the longitudinal interdimer interface of the tubulin heterodimer.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…An Arabidopsis phs1-1d allele was isolated as a gain-of-function mutant that displayed partial destabilization of cortical MTs and possessed a missense mutation in the putative kinase-interacting motif of a MPK phosphatase . Null alleles of PHS1 are phenotypically indistinguishable from the wild type under standard growth conditions (Pytela et al 2010), but do not induce MT depolymerization upon hyperosmotic stress (Fujita et al 2013). In addition to the MPK phosphatase domain, PHS1 contains an atypical kinase domain that phosphorylates Thr349 of a-tubulin (Fujita et al 2013).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TUA phosphorylation at this residue was shown to influence overall microtubule stability (Fujita et al, 2013). This previous work showed that TUA phosphorylation occurred under osmotic stress conditions and resulted in a polymerizationincompetent protein isoform that contributed to microtubule destabilization and depolymerization (Ban et al, 2013;Fujita et al, 2013).…”
Section: Tubulin Phosphorylationmentioning
confidence: 99%
“…19 NaCl/osmotic stress induces transient depolymerization and repolymerization of microtubules, which is essential for stress acclimation 20,21 and triggered by tubulin kinase PHS1. 22 Because CSCs associate with cortical microtubules via the CSI1/POM2 protein, 23,24 and microtubules are required for both, guiding CSCs at the PM as well as their secretion and internalization, 19,25 stress-induced microtubule depolymerization likely results in transient disruption of CSC and KOR1 organization. Perhaps, re-establishing microtubule-association of CSCs and KOR1 are essential steps for recovery from the salt shock and resuming growth under persisting salt stress.…”
mentioning
confidence: 99%